MicroRNA-505, Suppressed by Oncogenic Long Non-coding RNA LINC01448, Acts as a Novel Suppressor of Glycolysis and Tumor Progression Through Inhibiting HK2 Expression in Pancreatic Cancer - Xu, Zhenglei; Zhang, Dingguo; Zhang, Zhuliang; Luo, Weixiang; Shi, Ruiyue; Yao, Jun; Li, Defeng; Wang, Lisheng; Liao, Bihong (Frontiers in Cell and Developmental Biology, 2021)
Background MicroRNAs (miRNAs) and long non-coding RNAs (lncRNAs) play vital regulatory roles in pancreatic cancer (PC) initiation and progression. We aimed to explore the biological functions and underlying mechanisms of miR-505-3p (miR-505) in PC. Methods We first screened miRNA expression profiles using microarray in PC tissues and normal tissues, and then studied the function and underlying mechanism of miR-505. Moreover, we evaluated the regulatory effect of lncRNA LINC01448 on miR-505. Results We demonstrated miR-505 that was significantly downregulated in PC tissues. We further revealed that miR-505 significantly inhibited cell proliferation, invasion, sphere formation, glucose consumption and lactate production by targeting HK2. In addition, overexpression of miR-505 led to tumor growth inhibition in vivo, demonstrating that it acts as a tumor suppressor in PC. LINC01448 was identified as an oncogenic lncRNA that could reduce miR-505 expression. Subsequent studies confirmed that LINC01448 enhanced cell proliferation, invasion, sphere formation, glucose consumption and lactate production by regulating the miR-505/HK2 pathway. Conclusions These findings demonstrated that miR-505, suppressed by LINC01448, could function as a key tumor suppressor by targeting HK2 in PC, elucidating an important role of the LINC01448/miR-505/HK2 pathway in regulating PC glycolysis and progression.